Blockchain-powered fish industry: Trust perceptions of final consumers on traceable information availability - Tokkozhina, U.; Martins, A.; Ferreira, J. (Intelligent Transport Systems: 7th EAI International Conference, INTSYS 2023, Proceedings, 2024)
Blockchain is being actively discussed for business applications to digitalise supply chains. The still nascent level of blockchain adoption creates a difficulty to see the potential value that it may add to products and final consumers. Through a quantitative method, this study explores the impact of the traceability feature of products on the trust in the seller supermarket chain from the perspective of final consumers. Data from 417 questionnaires applied to buyers of fish was used to analyse such relation. Findings reveal the interest of final consumers towards traceable products and a positive relationship between the traceable information availability and the trust towards product.